Preparation method and application of self-modified iron-based material for removing heavy metals and organic pollutants
Through the synthetic and modified iron-based secondary mineral materials by acidophilic bacteria, the problem of low treatment efficiency of heavy metals and organic pollutants in wastewater in the prior art is solved, and efficient and stable pollutant removal and material recycling are achieved.
Patent Information
- Application Number
- CN202411504883.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-27
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-10-27
AI Technical Summary
The prior art is not efficient when treating heavy metals and organic pollutants in wastewater, and traditional methods such as Fenton oxidation have problems such as pH limit, large amount of iron sludge production, and the inability to reuse the catalyst.
Iron-based secondary minerals are synthesized by acidophilic bacteria, and the material is self-modified by pyrolysis or addition of aluminum ions to form a self-modified iron-based material with efficient removal of heavy metals and catalytic Fenton-like reaction to degrade organic pollutants.
It has achieved efficient removal of heavy metals and organic pollutants, the material has strong circulation ability, can be used multiple times, and can achieve complete degradation and mineralization of low concentrations of difficult-to-treat organic pollutants.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wastewater treatment, and specifically relates to a preparation method of a self-modified iron-based material for removing heavy metal pollutants and organic pollutants, and its application in the treatment of heavy metal and organic pollutant wastewater. Background Art
[0002] The pollution of heavy metals and organic matter in wastewater is widespread around the world. Heavy metal pollution has become a hot topic in environmental governance research due to its acute toxicity, non-biodegradability and bioaccumulation. Taking heavy metal chromium as an example, chromate passivation is usually used to slow down the corrosion rate of metal surfaces in cooling circuits, chromite mining, electroplating and other processes; in addition, wood processing, textile printing and dyeing, pigments and leather processing industries all use chromate as raw materials for production, and these industrial processes will produce a large amount of chromium-containing wastewater. Hexavalent chromium in the natural environment is toxic and difficult to degrade, and has potential toxic effects on the human body through enrichment in the food chain. Hexavalent chromium can cause irreversible changes in the structure of human proteins, thereby affecting the function of tissue cells and human health. Other common heavy metals, such as Cu(II), Zn(II), Cd(II), Pb(II), and As(III), also have similar properties.
[0003] Typical organic pollution includes antibiotic pollution and printing and dyeing wastewater. Antibiotics are often discharged into the water environment through medical wastewater, aquaculture wastewater, agricultural wastewater, etc., which may lead to the spread of antibiotic resistance genes, the disorder of aquatic ecosystems, and even pose a potential threat to human health. 12 H 14 Take florfenicol (FNO4S) as an example. This is a broad-spectrum antibiotic widely used to treat animal infectious diseases and is commonly used in fishery and poultry husbandry. Unmetabolized florfenicol will be discharged into the environment with animal feces and urine. It has biological toxicity and can cause various damages to organisms. At the same time, it is stable and difficult to hydrolyze spontaneously. The characteristics of printing and dyeing wastewater include high COD content, high SS concentration, complex composition, and biological toxic substances. It has large water volume, large water quality changes, high chromaticity, and large pH fluctuations, which affect the biochemical treatment effect and intermittent discharge. These characteristics lead to high treatment costs and great difficulty in management. Due to technical and economic reasons, most biological and physical treatment methods can only meet basic emission requirements. Organic matter is only decomposed into smaller substances. The properties of these decomposition products are difficult to control and grasp, and there is no guarantee that they will not cause harm to the environment. The current strategies for treating organic pollutants in wastewater include physical adsorption, biodegradation, and electrochemical degradation, which are sometimes not very effective. In recent years, the removal of pollutants by Fenton oxidation has been a major research hotspot in the field of wastewater treatment. This method refers to the reaction of H2O2 with Fe 2+ In the mixed system, Fe 2+The chain reaction is triggered to catalyze the decomposition of H2O2, and various active oxygen species are produced during the decomposition process, which attack the difficult-to-degrade compounds and cause them to break bonds or open rings. The main problems of the Fenton method for treating wastewater are strict pH restrictions and large amounts of iron sludge, and the catalyst cannot be reused, resulting in a waste of reagents.
[0004] In view of the problem that traditional water treatment methods are inefficient in treating heavy metal pollutants and organic pollutants, the present invention proposes a method for synthesizing and improving iron-based secondary minerals using acidophilic bacteria.
[0005] In acidic mine wastewater, there are many types of acidophilic bacteria that can synthesize iron-based secondary minerals. For example, Acidithioobacillus ferrooxidans can promote the oxidation of low-valent iron in the environment, causing it to aggregate, while its extracellular macromolecules (such as polysaccharides and proteins) can bind to the aggregated iron and deposit it into iron-based minerals. This bacterium can accelerate the oxidation of ferrous ions in an acidic environment, increasing the oxidation rate to 10 times that of a sterile environment. 5 -10 8 times. The iron ions obtained by oxidation react with various anions in the mining environment (such as SO4 2- ) combined to form a large number of iron-based secondary minerals.
[0006] The present invention uses acidophilic bacteria to synthesize iron-based secondary mineral materials in an iron-containing culture medium, and self-modifies the materials through pyrolysis or addition of aluminum ions, resulting in morphological and component changes that are beneficial to the removal of heavy metals or catalytic Fenton reactions to degrade organic pollutants, and exhibits good heavy metal pollutant and organic pollutant removal performance in a relatively short period of time. Summary of the invention
[0007] In order to solve the above problems, the purpose of the present invention is to provide a self-modified iron-based material for removing heavy metal pollutants and organic pollutants, and a preparation method and application method thereof.
[0008] The present invention provides a method for preparing a self-modified iron-based material for removing heavy metal pollutants and organic pollutants, which comprises the following steps:
[0009] (1) adding the acidophilic bacterial cells with stable iron oxidation ability obtained by culture to a culture medium with a pH of 1.5-2.5, synthesizing iron-containing secondary minerals and then pyrolyzing them to form modified iron-based materials; or adding the bacterial cells to an iron-containing culture medium with aluminum ions added, synthesizing secondary minerals modified with aluminum sulfate and then pyrolyzing them to form aluminum ion-modified iron-based biomaterials;
[0010] The pyrolysis is carried out using a tubular furnace, with N2 flowing throughout the process to create a strict anaerobic environment, with a constant heating rate, and after reaching the target temperature, the temperature needs to be maintained constant and then slowly dropped to room temperature;
[0011] (2) After filtering, washing, drying and grinding, the self-modified iron-based material is obtained.
[0012] Specifically, the acidophilic bacteria must have the ability to oxidize iron and be selected from Acidithiobacillus ferrooxidans, Acidithiobacillus caldus, Leptospirillum ferriphilum, Leptospirillumferrooxidans, and the like.
[0013] Among them, the synthetic iron-based secondary minerals are weakly crystalline iron-containing sulfate hydroxyl minerals, such as jarosite, Schottkynerite, ammonium jarosite, etc.
[0014] In a specific embodiment, during the expansion culture of the acidophilic bacteria with stable iron oxidation ability, the initial pH of the culture medium is 1.5-2.5, the temperature during the process is 25-45°C, the rotation speed is 170-200rpm, and the time is 2-4 days; after the expansion culture is completed, the bacteria are collected by centrifugation, washed with deionized water with pH 1.5-2.5, mixed and then used in the subsequent steps;
[0015] More specifically, a 9K medium (3 g / L (NH4)2SO4, 0.5 g / L K2HPO4, 0.1 g / L KCl, 0.5 g / L MgSO4·7H2O) with a pH of 2 and FeSO4·7H2O added as an energy source was used, and the culture was expanded to the logarithmic phase in a shaker at 30°C and 180 rpm, and the culture was centrifuged in a low-temperature centrifuge at 10,000 rpm for 15 min, and the solids were filtered out and washed with sterile water at pH of 2 for later use;
[0016] When synthesizing the material, the initial pH of the culture medium is 1.5-2.5, the temperature during the process is 25-45° C., the rotation speed is 170-200 rpm, and the time is 6-8 days.
[0017] Preferably, in step (1), the pH is adjusted to pH=1.5-2.5 using sulfuric acid, Fe(NH4)2(SO4)2·6H2O is added to the culture medium for synthesizing ammonium jarosite, FeSO4·7H2O, K2SO4 is added to the culture medium for synthesizing jarosite, or FeSO4·7H2O is added to the 9K culture medium, and FeSO4·7H2O is added to the culture medium for synthesizing Schottkynerite;
[0018] The pyrolysis operation is carried out in a tubular furnace with N2 flowing throughout the process. The material is heated to 450-550°C over 60-70 minutes. The temperature is kept rising at a steady rate during the heating process. After reaching the target temperature, the temperature is kept constant for 90-150 minutes; then the temperature is slowly lowered to room temperature; when synthesizing secondary minerals modified with aluminum sulfate, aluminum sulfate is added in an Al:Fe ratio of 0.1:1 to 1:1.
[0019] In a specific embodiment, after the material is synthesized, the material is collected by filtration, washed with deionized water with a pH of 1.5-2.5, and dried at a low temperature in a vacuum drying oven; and ground using an agate mortar.
[0020] The invention provides a preparation method for obtaining a self-modified iron-based material.
[0021] The present invention also provides the use of the self-modified iron-based material in removing heavy metals or organic pollutants in water bodies. Specifically, the heavy metal is one or more of Cr(VI), Cu(II), Zn(II), Cd(II), Pb(II) and As(III); the organic pollutants are one or more of antibiotics such as florfenicol, chloramphenicol, tetracycline, and dyes such as rhodamine B and methylene blue.
[0022] The present invention further provides a method for removing heavy metal pollution in water, which comprises adding the self-modified iron-based material to waste liquid containing heavy metals, the operating temperature is 20-40°C, the initial pH value is 3-11, the rotation speed is 170-200rpm, the treatment time is 20-120min, and the treated waste liquid and material are separated by centrifugation;
[0023] Alternatively, the modified iron-based material is added to the waste liquid containing organic pollutants for removal under the condition of adding strong oxidants such as hydrogen peroxide or persulfate, the operating temperature is 20-40°C, the initial pH value is 3-9, the rotation speed is 170-200rpm, the treatment time is 20-240min, and the treated waste liquid and material are separated by centrifugation;
[0024] Specifically, after use, the modified iron-based material is rinsed with a pH 1.5-2.5 aqueous solution and then recycled, for example, 2-6 times.
[0025] Due to the adoption of the above scheme, the beneficial effects of the present invention are:
[0026] The steps for preparing the self-modified iron-based material of the present invention are simple and clear, and the reagents and methods used are relatively cheap and easy to obtain, which is convenient for large-scale industrial production; the modified iron-based material prepared by the present invention has high and stable removal efficiency for heavy metals and organic pollutants, and is less affected by pH, environmental ions and organic matter. The modified iron-based material prepared by the present invention has a strong circulation capacity and can be used multiple times after filtering, washing and drying. The modified iron-based material prepared by the present invention can achieve complete degradation and mineralization of low-concentration difficult-to-treat organic pollutants. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The scanning electron microscope images of modified ammonium ferrosite and jarosite at different pyrolysis temperatures in the present invention are shown. In the figure, the unmodified biosynthesized ammonium ferrosite is named A1, the unmodified jarosite is named A2, the ammonium ferrosite modified at 500°C is named B1, the jarosite modified at 500°C is named B2, the ammonium ferrosite modified at 200°C is named F1, the jarosite modified at 200°C is named F2, the ammonium ferrosite modified at 900°C is named F3, and the jarosite modified at 900°C is named F4.
[0028] Figure 2 The XPS graphs of Fe and S elements of ammonium ferrosite and jarosite before and after 500°C pyrolysis modification in the present invention are shown in the figure. In the figure, a and b are ammonium ferrosite before modification, A and B are ammonium ferrosite after 500°C pyrolysis modification; c and d are jarosite before modification, C and D are jarosite after 500°C pyrolysis modification, and a, c, A and C are Fe2p, and b, d, B and D are S2p.
[0029] Figure 3 The scanning electron microscope images of jarosite and Schottkynerite with and without aluminum sulfate modification in the present invention are shown. Each group of electron microscope images are from left to right of the same material at different magnifications under a scanning electron microscope.
[0030] Figure 4 The 200°C and 900°C thermally modified materials in the present invention are time versus Cr(VI)C / C0 curves within 120 min and the final pH, wherein Aj is ammonium jarosite, J is jarosite, and the numbers represent the modification temperature.
[0031] Figure 5 The Cr(VI)C / C0 curves of the modified (note N2 in the figure) and unmodified ammonium jarosite and jarosite at 500°C within 120 minutes in the present invention.
[0032] Figure 6The C / C0 curve of the florfenicol concentration in 240 min of the modified materials with different Al:Fe ratios in the present invention under the addition of H2O2 or PMS. The numbers in the legend represent the Al:Fe ratio. In the figure, A and B are added with H2O2, C and D are added with PMS; A and C are added with different aluminum sulfate modified jarosite (Jar), B and D are added with different aluminum sulfate modified Schwitzite (Sch).
[0033] Figure 7 The C / C0 curve of the modified materials with different Al:Fe ratios in the present invention within 180 minutes versus the concentration of Rhodamine B is shown in the figure. The numbers in brackets in the legend represent the Al:Fe ratio. In the figure, AC is the performance of aluminum sulfate-modified Schrebert mineral in removing Rhodamine B under the addition of PDS, PMS and H2O2, respectively, and DF is the change of reactants PDS, PMS and H2O2 in the aluminum sulfate-modified Schrebert mineral catalytic system; ac is the performance of aluminum sulfate-modified yellow potassium ferrosite in removing Rhodamine B under the addition of PDS, PMS and H2O2, respectively, and df is the change of reactants PDS, PMS and H2O2 in the aluminum sulfate-modified yellow potassium ferrosite catalytic system.
[0034] Figure 8 The Cr(VI)C / C0 curve and the final pH value of the modified ammonium yttrium ferrocyanide at 500°C for 120 min.
[0035] Fig. 9 The C / C0 curve of florfenicol concentration within 180 min for modified jarosite and Schreiberite of Al:Fe=0.5:1 in the present invention under different initial pH values when H2O2 is added.
[0036] Fig.10 The Cr(VI)C / C0 curves of the modified ammonium yttrium ferrocyanide at 500°C for 120 min under different anion addition conditions.
[0037] Fig.11 The BC / C0 curves of rhodamine in 120 min for Al:Fe=0.5:1 modified Schottkynerite (AI) and Al:Fe=1:1 modified jarosite (AI) under different anion addition conditions are shown in the figure.
[0038] Fig.12 The Cr(VI)C / C0 curves of the modified ammonium yttrium ferrocyanide at 500°C for 120 min under different organic acid addition conditions. DETAILED DESCRIPTION
[0039] The present invention will be further described below with reference to the accompanying drawings and specific examples, but the present invention is not limited thereto.
[0040] Example 1
[0041] The method for preparing a self-modified iron-based material for removing heavy metal pollutants and organic pollutants in this embodiment comprises the following steps:
[0042] (1) Expansion of strains for synthesizing iron-based materials
[0043] FeSO4·7H2O was added to 9K medium to make the final concentration of FeSO4·7H2O 44.78 g / L, and the pH was adjusted to 2 with sulfuric acid. Acidithiobacillusferrooxidans with stable iron oxidation ability was cultured in a shaker at 30°C and 180 rpm until the logarithmic growth phase (about 3 days). After filtering out the solids, centrifuge at 10000 rpm for 15 minutes, collect the bacteria, wash twice with sterile water at pH = 2.0, add a little sterile water at pH = 2, and obtain a bacterial suspension.
[0044] (2) Iron-based material synthesis and modification are carried out separately
[0045] The synthesis and modification of materials for heavy metal pollutant removal are carried out separately. The specific steps are:
[0046] Add 250mL of deionized water with pH=2 to a 500mL shaking flask, and then add an equal amount of bacterial suspension. Divide the shaking flasks into groups, add 25g of Fe(NH4)2(SO4)2·6H2O to each flask in one group to synthesize ammonium jasperite; add 11.12g of FeSO4·7H2O and 1.16g of K2SO4 to the other group to synthesize yellow jarosite. After culturing in a shaking incubator at 30℃ and 180rpm for 7 days, collect the synthesized product by filtration, wash it 3 times with deionized water with pH=2.0, and dry it in a vacuum drying oven.
[0047] The dried jarosite and ammonium jarosite were thermally modified in a tubular furnace. With nitrogen flowing steadily throughout the process, the materials were heated from room temperature to 200°C in 24 minutes, to 500°C in 65 minutes, and to 900°C in 120 minutes. The temperature was kept rising steadily during the heating process. After reaching the target temperature, the temperature was kept constant for 120 minutes. Then the temperature was slowly lowered to room temperature. Finally, six thermally modified materials were obtained under a nitrogen environment.
[0048] The scanning electron microscope spectra of eight materials before and after modification are shown in Figure 2. Figure 1As shown, the unmodified biosynthetic ammonium jasonite was named A1, the unmodified jarosite was named A2, the ammonium jasonite modified at 500°C was named B1, the jarosite modified at 500°C was named B2, the ammonium jasonite modified at 200°C was named F1, the jarosite modified at 200°C was named F2, the ammonium jasonite modified at 900°C was named F3, and the jarosite modified at 900°C was named F4.
[0049] Figure 2 The XPS results of Fe and S of the material before and after 500℃ pyrolysis modification are shown. The existence form of Fe element in biosynthesized ammonium jarosite and jarosite has changed significantly. XPS detected the newly appeared Fe(II), and according to the peak area analysis, its proportion in the total iron is greater than that of Fe(III). Compared with the modified jarosite, the Fe(II) ratio of the modified ammonium jarosite is higher. Before and after modification, sulfate is the main existence form of S.
[0050] (3) Synthesis and modification of materials for organic pollutant removal are carried out simultaneously
[0051] The specific steps are:
[0052] Add 300 mL of 9K medium with pH = 2 to a 500 mL shake flask, then add 35 g of FeSO4·7H2O, and then add an equal amount of bacterial suspension to the shake flask. Divide the shake flask into 4 groups, add different masses of Al2(SO4)3·12H2O (calculate the amount of aluminum sulfate with Al:Fe ratio of 0:1, 0.1:1, 0.5:1, 1:1) to synthesize aluminum sulfate-modified iron-based biomaterials with different morphologies and sizes. After culturing in a shaker at 30°C and 180 rpm for 7 days, filter and collect the synthesis, and put it into a vacuum drying oven for drying.
[0053] The morphology of Schmidt mineral and jarosite without and with aluminum sulfate under scanning electron microscope is as follows: Figure 3 As shown, it can be seen that the material in the aluminum sulfate addition system undergoes obvious morphological changes.
[0054] Example 2
[0055] This example is used to illustrate the effect of different pyrolysis temperatures on the removal of heavy metal pollutants by modified materials. 8.5 g of potassium dichromate was added to 1 L of deionized water to prepare a 3 g / L Cr(VI) solution. 96.5 ml of deionized water was added to a 150 ml conical flask, and then 3.5 ml of Cr(VI) solution was added to form a 105 mg / L chromium solution system.
[0056] 0.1 g of each of the iron-based materials prepared by heat modification at six different temperatures for heavy metal removal synthesized in Example 1 was added to the above-mentioned conical flask, and the reaction was carried out in a constant temperature shaking shaker at 30°C and a rotation speed of 180 rpm. Samples were taken every 10 minutes from 0 to 40 minutes, and every 20 minutes after 40 minutes, with 1 mL taken each time, and the supernatant was collected by centrifugation. The Cr(VI) concentration was determined using diphenylcarbazide spectrophotometry. After the reaction was completed for 120 minutes, the pH of the reaction system was measured.
[0057] Depend on Figure 4 , the Cr(VI) removal rate within 100 min of pyrolysis modification at 200℃ and 900℃ was only about 20%.
[0058] Depend on Figure 5 The Cr(VI) removal rate of 500℃ thermally modified jarosite within 120 minutes reached 70%, and the Cr(VI) removal rate of 500℃ thermally modified ammonium jarosite within 120 minutes reached more than 90%, and the maximum removal rate was reached in about 20 minutes, showing a good Cr(VI) removal effect.
[0059] Example 3
[0060] This example aims at removing organic pollution from modified iron-based minerals and explores the effect of different aluminum sulfate dosages on the removal of organic pollutants such as antibiotic florfenicol and dye rhodamine B by the material.
[0061] (1) Effect of different aluminum sulfate dosages on the removal of florfenicol by materials.
[0062] Add 10 mg of florfenicol to 1 L of ultrapure water to prepare a 10 mg / L florfenicol solution. Ultrasonicate for 1.5 h to allow florfenicol to be evenly and fully dissolved in water. Take 100 mL each time and pour it into a 250 mL conical flask. Prepare 0.5 M permonosulfate (PMS) and 0.5 M H2O2 solutions.
[0063] The above-mentioned conical flask is divided into PMS and H2O2 groups. 0.1g of each of the eight kinds of iron-based materials synthesized in different aluminum sulfate medium for organic pollutant removal synthesized in Example 1 is added to the above-mentioned conical flask, and 1mL of PMS or H2O2 mother liquor is added according to the conical flask group. The reaction is carried out in a constant temperature shaking shaker at 30°C and a speed of 180rpm. After adding the oxidant, the timing is immediately started. The total reaction time is 4 hours, and a sample is taken every 40min. Each time 0.75mL of the sample solution is taken to 0.75mL of pure methanol solution and then immediately shaken to quench the free radical reaction. The filtrate is collected through a 0.22μm organic filter membrane, and pure methanol and ultrapure water are used as mobile phases. High performance liquid chromatography (HPLC) is used to detect at 220nm to determine the concentration of florfenicol in the sample solution.
[0064] Depend on Figure 6 , Al:Fe=1:1 and 0.5:1 aluminum sulfate modified Schreiberite had the best effect on catalyzing H2O2 / PMS to degrade florfenicol, and other modified materials also showed excellent catalytic degradation ability.
[0065] (2) The effect of different aluminum sulfate dosages on the removal of rhodamine B by the material.
[0066] Add 50 mg of rhodamine B to 1 L of deionized water to prepare a 50 mg / L rhodamine B solution, and pour 100 mL each time into a 250 mL conical flask. Prepare 0.5 M peroxydisulfate (PDS), 0.5 M peroxymonosulfate (PMS) and 10 g / L H2O2 solution.
[0067] The above-mentioned conical flasks are divided into three groups, namely PDS, PMS, and H2O2 groups. 0.1g of each of the eight iron-based materials synthesized by adding different aluminum sulfates for the removal of organic pollutants synthesized in Example 1 is added to the above-mentioned conical flasks, and then 1mL of PDS or PMS or H2O2 mother liquor is added according to the conical flask groups. The reaction is carried out in a constant temperature shaking shaker at 30°C and a speed of 180rpm. After adding the oxidant, the timing is immediately started. The total reaction time is 3 hours, and samples are taken every 30 minutes. Each time 0.75mL of the sample solution is taken into 0.75mL of pure methanol solution and then immediately shaken to quench the free radical reaction. The filtrate is collected through a 0.22μm organic filter membrane, and the absorbance is detected by a spectrophotometer at 554nm to determine the concentration of rhodamine B in the sample solution.
[0068] Depend on Figure 7 It can be seen that aluminum sulfate-modified Schroeder mineral and jarosite both showed good efficiency in catalyzing PMS / PDS to degrade rhodamine B. Among the modified Schroeder minerals, Al:Fe=1:1 had the best effect in catalyzing hydrogen peroxide to degrade rhodamine B.
[0069] Example 4
[0070] This example is used to illustrate the effect of initial pH on the removal of heavy metal pollutants and organic pollutants by modified materials.
[0071] (1) Effect of initial pH on the removal of heavy metal chromium by materials
[0072] First, dilute 3g / L potassium dichromate solution to 105mg / L, adjust the pH to 3, 5, 7, 9, and 11 with NaOH and dilute sulfuric acid solution, and set up parallel experimental groups. Weigh 0.1g of 500℃ thermally modified ammonium yttrium ferroaluminate and add it to each reaction system. Subsequent operations are the same as in Example 2.
[0073] Depend on Figure 8It can be seen that when the initial pH range of the 500°C thermally modified ammonium jasper prepared by the present invention is 3-11, the Cr(VI) removal effect in the water environment is not greatly affected by the pH, and it has good hexavalent chromium removal performance. After 100 minutes, the pH at the end of the experiment is as shown in the figure.
[0074] (2) Effect of initial pH on the removal of organic pollutant florfenicol by materials
[0075] Add 10 mg of florfenicol to 1 L of ultrapure water to prepare a 10 mg / L florfenicol solution, and ultrasonicate for 1.5 h to allow florfenicol to be evenly and fully dissolved in water. Pour 100 mL each time into a 250 mL conical flask, and adjust the pH to 3, 5, 7, 9, or 11 with NaOH and dilute sulfuric acid solution. Prepare a 0.5 M H2O2 solution.
[0076] 0.1 g of each of the aluminum sulfate-modified jarosite (named Jar0.5) and the modified Schwarzschild mineral (named Sch0.5) with Al:Fe=0.5:1 for organic pollutant removal synthesized in Example 1 was added to the above-mentioned conical flask, and then 1 mL of H2O2 mother liquor was added respectively. The total reaction time was 3 hours, and samples were taken every 30 minutes. Other operations were the same as Example 2 (1).
[0077] Depend on Fig. 9 It can be seen that the catalytic degradation efficiency of florfenicol by aluminum sulfate-modified jarosite was excellent at the initial pH = 3, which decreased at pH = 5 and was strongly inhibited after pH ≥ 7.
[0078] Depend on Fig. 9 It can be seen that the aluminum sulfate-modified Schreiber mineral has excellent catalytic degradation efficiency of florfenicol at the initial pH = 3-9, and almost complete degradation is achieved within 30 minutes. The catalytic degradation efficiency decreases at pH = 11.
[0079] Example 5
[0080] Various anions are commonly found in water environments rich in heavy metals and organic pollutants. This example explores the effects of common anions in the environment on the removal of heavy metal pollutants and organic pollutants by the material.
[0081] (1) Effect of anions on the removal of heavy metal chromium from materials
[0082] First, dilute the 3g / L potassium dichromate solution to 105mg / L, then add NaCl, NaHCO3, NaH2PO4, and NaNO3 mother liquors respectively to make the final concentration of the corresponding anions in the system 20mg / L, weigh 0.1g of 500℃ heat-modified ammonium yttrium and add it to each reaction system respectively, and the subsequent operations are the same as Example 2.
[0083] Depend on Fig.10 It can be seen that the addition of the four anions has little effect on the chromium removal effect. Nitrate has a certain inhibitory effect on the chromium removal of the material, while the other three anions have no effect. This shows that the material prepared by the present invention has a strong resistance to complex anion environments, and most common anions will not affect the chromium removal efficiency of the material.
[0084] (2) Effect of anions on the removal of organic pollutant Rhodamine B by materials
[0085] 50 mg of rhodamine B was added to 1 L of deionized water to prepare a 50 mg / L rhodamine B solution, and 100 mL was measured and poured into a 250 mL conical flask each time. The conical flasks were divided into three groups, and Na2SO4, NaNO3, and NaCl were added to test the effects of sulfate, nitrate, and chloride ions on the removal of rhodamine B by the material. Two final concentrations of each salt were set: 0.5 mM and 1 mM.
[0086] Prepare 0.5 M peroxydisulfate (PDS), 0.5 M peroxymonosulfate (PMS) and 10 g / L H2O2 solutions.
[0087] Each large group of conical flasks was divided into three small groups, namely PDS, PMS, and H2O2 groups. 0.1 g of aluminum sulfate modified jarosite (named Jar0.5) with Al:Fe=0.5:1 and modified Schwarzschild mineral (named Sch1) with Al:Fe=1:1 for organic pollutant removal synthesized in Example 1 were added to each reaction system, and the subsequent operations were the same as in Example 3(2).
[0088] Depend on Fig.11 It can be seen that when chloride ions exist, it strongly promotes the degradation of rhodamine B by PMS catalyzed by aluminum sulfate modified Schreiner mineral, while sulfate ions and nitrate ions have little effect on the reaction; when the three anions exist, it has a certain inhibitory effect on the degradation of rhodamine B by PDS catalyzed by modified Schreiner mineral; when chloride ions exist, it has a certain inhibitory effect on the degradation of rhodamine B by H2O2 catalyzed by modified Schreiner mineral, while the presence of sulfate and nitrate ions has no significant inhibitory effect on the reaction.
[0089] Depend on Fig.11 It can be seen that the presence of the three anions has little effect or a promoting effect on the degradation of rhodamine B by PMS / PDS / H2O2 catalyzed by aluminum sulfate-modified jarosite.
[0090] Example 6
[0091] There are some types of organic acids in various industrial wastewater environments. This example is used to illustrate the effect of organic acids on the removal of heavy metal pollutants and organic pollutants by modified materials. First, dilute 3g / L potassium dichromate solution to 105mg / L, then add different concentrations of humic acid (HA) mother liquor to make the final concentration of humic acid in the system 10, 20, 30, 40mg / L and citric acid (CA) and oxalic acid (OA) mother liquor to make the final concentration of organic acid in the system 20mg / L, and the subsequent operation is the same as Example 2. A control group of 40mg / L humic acid is set up, and no material is added as the control group.
[0092] Depend on Fig.12 It can be seen that the three organic acids have no absolute effect on the removal effect of hexavalent chromium of this material, the concentration of humic acid has no correlation with the removal effect of the material on chromium, and citric acid can promote the removal of chromium to a certain extent.
Claims
1. A method for preparing a self-modified iron-based material for removing heavy metal pollutants and organic pollutants, characterized in that: The following steps are involved: (1) adding the acidophilic bacteria with stable iron oxidation ability obtained by culture to a culture medium with a pH of 1.5-2.5, synthesizing iron-containing secondary minerals and then pyrolyzing them to form modified iron-based materials; or adding the bacterial cells to an iron-containing culture medium supplemented with aluminum ions, synthesizing secondary minerals modified with aluminum sulfate, and then pyrolyzing them to form aluminum ion-modified iron-based biomaterials; The pyrolysis is carried out using a tubular furnace, with N2 flowing throughout the process to create a strict anaerobic environment, with a constant heating rate, and after reaching the target temperature, the temperature needs to be maintained constant and then slowly dropped to room temperature; (2) After filtering, washing, drying and grinding, the self-modified iron-based material is obtained.
2. The preparation method according to claim 1, characterized in that: Acidophilic bacteria need to have iron oxidation ability, selected from Acidithiobacillus ferrooxidans, Acidithiobacillus caldus, Leptospirillum ferriphilum, Leptospirillum ferrooxidans .
3. The preparation method according to claim 1, characterized in that: The synthetic iron-based secondary minerals are weakly crystalline iron-containing sulfate hydroxyl minerals, such as jarosite, schmidtite, ammonium jarosite, etc.
4. The preparation method according to claim 1, characterized in that: When the acidophilic bacteria with stable iron oxidation ability are expanded, the initial pH of the culture medium is 1.5-2.5, the temperature during the process is 25-45° C., the rotation speed is 170-200 rpm, and the time is 2-4 days; after the expansion culture is completed, the bacteria are collected by centrifugation, washed with deionized water with pH 1.5-2.5, mixed and then used in the subsequent steps; More specifically, a 9K medium (3 g / L (NH4)2SO4, 0.5 g / LK2HPO4, 0.1 g / L KCl, 0.5 g / L MgSO4·7H2O) with a pH of 2 and FeSO4·7H2O added as an energy source was used, and the culture was expanded to the logarithmic phase in a shaker at 30°C and 180 rpm, and centrifuged in a low-temperature centrifuge at 10,000 rpm for 15 min, and after filtering out solids, the culture was washed with sterile water with a pH of 2 for later use; When synthesizing the material, the initial pH of the culture medium is 1.5-2.5, the temperature during the process is 25-45° C., the rotation speed is 170-200 rpm, and the time is 6-8 days.
5. The preparation method according to claim 4, characterized in that: In step (1), the pH is adjusted to pH=1.5-2.5 using sulfuric acid, Fe(NH4)2(SO4)2·6H2O is added to the culture medium for synthesizing ammonium ferric alum, FeSO4·7H2O, K2SO4 is added to the culture medium for synthesizing jarosite, or FeSO4·7H2O is added to the 9K culture medium, and FeSO4·7H2O is added to the culture medium for synthesizing Schottkynerite; The pyrolysis operation is carried out in a tubular furnace with N2 flowing throughout the process. The material is heated to 450-550°C over 60-70 minutes. The temperature is kept rising at a steady rate during the heating process. After reaching the target temperature, the temperature is kept constant for 90-150 minutes; then the temperature is slowly lowered to room temperature; when synthesizing secondary minerals modified with aluminum sulfate, aluminum sulfate is added in an Al:Fe ratio of 0.1:1 to 1:
1.
6. The preparation method according to claim 1, characterized in that: After the material is synthesized, the material is collected by filtration, washed with deionized water with a pH of 1.5-2.5, and dried at low temperature in a vacuum drying oven; an agate mortar is used for grinding.
7. A self-modified iron-based material obtained by the preparation method according to any one of claims 1 to 6.
8. Use of the self-modified iron-based material according to claim 7 in removing heavy metals or organic pollutants in water bodies, specifically, the heavy metal is one or more of Cr(VI), Cu(II), Zn(II), Cd(II), Pb(II) and As(III); the organic pollutants are one or more of antibiotics such as florfenicol, chloramphenicol, tetracycline and dyes such as rhodamine B and methylene blue.
9. A method for removing heavy metal pollution in water, characterized in that: The self-modified iron-based material is added to the waste liquid containing heavy metals, the operating temperature is 20-40°C, the initial pH value is 3-11, the rotation speed is 170-200rpm, the treatment time is 20-120min, and the treated waste liquid and material are separated by centrifugation; Alternatively, the modified iron-based material is added to the waste liquid containing organic pollutants for removal under the condition of adding strong oxidants such as hydrogen peroxide or persulfate. The operating temperature is 20-40°C, the initial pH value is 3-9, the rotation speed is 170-200rpm, the treatment time is 20-240min, and the treated waste liquid and material are separated by centrifugation.
10. The method according to claim 9, characterized in that After use, the modified iron-based material is rinsed with a pH 1.5-2.5 aqueous solution and then recycled, for example, 2-6 times.
Citation Information
Patent Citations
Aluminum sulfate modified iron-based biological material for heavy metal adsorption and preparing and application method thereof
CN104525144A
Biological heavy metal contaminated soil remediation agent as well as preparation method and application thereof
CN112342029A
Preparation and application of coralline Schwertmannite with activation and passivation functions
CN113428965A
Preparation and application of carbon-coated iron oxide of high-mediation oxalic acid reduced chromium
CN114308038A
Biosynthesis method for exogenous seed crystal-added mediated schwertmannite, as well as product and application of schwertmannite
WO2023207005A1